MicroRNAs That Promote or Inhibit Memory Formation in Drosophila melanogaster. Issue 2 (3rd June 2015) - Busto, Germain U; Guven-Ozkan, Tugba; Fulga, Tudor A; Van Vactor, David; Davis, Ronald L
Abstract: microRNAs (miRNAs) are small noncoding RNAs that regulate gene expression post-transcriptionally. Prior studies have shown that they regulate numerous physiological processes critical for normal development, cellular growth control, and organismal behavior. Here, we systematically surveyed 134 different miRNAs for roles in olfactory learning and memory formation using "sponge" technology to titrate their activity broadly in the Drosophila melanogaster central nervous system. We identified at least five different miRNAs involved in memory formation or retention from this large screen, including miR-9c, miR-31a, miR-305, miR-974, and miR-980 . Surprisingly, the titration of some miRNAs increased memory, while the titration of others decreased memory. We performed more detailed experiments on two miRNAs, miR-974 and miR-31a, by mapping their roles to subpopulations of brain neurons and testing the functional involvement in memory of potential mRNA targets through bioinformatics and a RNA interference knockdown approach. This screen offers an important first step toward the comprehensive identification of all miRNAs and their potential targets that serve in gene regulatory networks important for normal learning and memory.